The Dynamics of Changes of the Copper Concentration in the Blood Serum in Patients with Craniocerebral Trauma of Mild and Moderate Severity in Peaceful Time and in Soldiers of Anti-terrorist Operation with Mine Explosive Brain Injury in Acute and Intermediate Periods - Zadorozhna B.; Shevaga V.; Semchyshyn М. (Львівський клінічний вісник)
Introduction. The problem of pathogenesis of craniocerebral trauma (CMT) is relevant in modern medicine. Particular attention is paid to the search for biochemical markers, due to the impossibility of holistic explanation of the occurrence of all the pathological manifestations of brain damage only due to its mechanical damage. One of such areas may be the study of mineral homeostasis, in particular, the exchange of copper. Aim. To study the level of trace element of copper in the blood serum of patients in the brain injury of mild and moderate severity and in soldiers of anti-terrorist operation with mine explosive brain injury during acute and intermediate periods. Materials and methods. Complex examination of 283 patients with brain injury of mild and moderate severity in acute and intermediate periods was carried out as well as of 218 soldiers of anti-terrorist operation with mine explosive craniocerebral trauma. 20 almost healthy volunteers made the control group for patients of a peaceful time and 20 soldiers of anti-terrorist operation with politrauma – for patients with mine explosive brain injury. The level of trace element of copper in the serum of blood was investigated by means of atomic – absorption spectroscopy. Results and discussion. The concentration of copper in the serum of blood examination on the 1-2, 3-5, 7-10, 14-21 days, and in 1 month after the trauma was found out. Analysis of the results examination show, that with all patients with brain injury on peaceful territory the concentration of copper in the serum of blood was reliably higher (p < 0.05) as compared with the control group during all the period of observation. The highest degree index was observed in patients with cerebral contusion of mild degree, the lowest – in patients with cerebral concussion. Critically high levels of copper were observed on 3-5 and 7-10 days, but in 1 month after trauma it reduced, however remained quite higher (p < 0.05) than the index in the comparison group. Analysis of dynamics changes of the copper concentration in soldiers of the anti-terrorist operation show, that in all the soldiers´ blood serum the contents of copper was significantly higher during all the observation period, as compared with the control group (p < 0.05), and also as compared to the received facts in the other group (р1 < 0.05, р2 < 0.05, р3 < 0.05). The essential difference in the contents of copper in the serum of blood was observed in the soldiers with cerebral contusion of mild severity and cerebral contusion of moderate severity, lessened by the cerebral concussion. Area of results application. Neurology. Conclusions. High indices of copper concentration in the serum of blood indicates about the vessel pathology and causes oxidative stress, that is a factor for sclerosis cerebral vessels.